Performing Both Sides of the Glass: Videogame Affordances and Live Streaming on Twitch - Howells, Lachlan Mark (Curtin University, 2023)
This thesis examines the performative dimensions videogame affordances assume within online, live streaming environments. This approach considers how streamers configure their videogame play in terms of a potential audience, drawing on five semi-structured, in-depth interviews with Australian-based Twitch streamers to analyse how streamers leverage videogame affordances to produce “meaningful moments”. Guiding this thesis is the question of how the player-videogame relationship is maintained, fractured or altered within live-streaming environments such as Twitch.